Menakar Keberadaan Tokoh Syekh Jamaluddin Al-Akbar Al-Husain di Tosora Wajo: Menelaah jejak keberadaan tokoh Syekh Jamaluddin Al-Akbar Al-Husain di Tosora-Wajo - Makmur, Makmur; Hadrawi, Muhlis; Purnamasari, Nurul Adliyah; Ramli, Muhammad; Hasanuddin, nfn.; Nasihin, nfn. (BRIN, 2023)
This study aims to examine the traces of presence of Syekh Jamaluddin al-Akbar al-Husain in Tosora Wajo as an Islamic religious propagator figure in the 13th and 14th centuries CE. Qualitative method with an interdisciplinary approach uses to obtain archaeological, philological, and anthropological data. Archaeological data is in the form of tombs, mosques, ceramics, pottery, coins, and various other artifacts. Philological data is in the form of Lontara Akkarungeng ri Wajo and Lontara Suqkuna Wajo manuscripts, as well as other important lontara manuscripts in South Sulawesi. Anthropological data in the form of collective memory and ethnography of people and the caretaker in the old mosque of Tosora-Wajo. The results of examination and interpretation of archaeological, philological, and anthropological data do not show any coherency with the traces of existence of Sheikh Jamaluddin al-Akbar al-Husain in Tosora-Wajo.